Limit cycles bifurcations of Liénard system with a hyperelliptic Hamiltonian of degree five - Yi Shao; Chunxiang A (Electronic Journal of Qualitative Theory of Differential Equations)
We deal with limit cycles bifurcating from the period annulus of Liénard system with a hyperelliptic Hamiltonian of degree five under quartic perturbation, where Liénard system has a normal form $\dot{x}=y$, $\dot{y}=x(x-1)(x^{2}+ax+b)$, $a^{2}-4b<0$. It is proved that the perturbation of this system can produce at most six limit cycles for $a=b=2$.